HPI INDONESIA'S PERSPECTIVE ON INHERITANCE THROUGH TESTAMENT BY INDONESIAN CITIZENS ABROAD - Prisca Dwi Maylinda (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
This study discusses the form of HPI protection and the legal consequences of inheritance through testament by Indonesian citizens abroad. This research is a juridical-normative research, using legal, conceptual, and comparative approaches. In this study, it was found that the form of HPI protection against testament making by Indonesian citizens abroad is the existence of Algemeine Bepalingen and the doctrine of experts, which Indonesia itself has not ratified, so it tends to adopt existing principles. This results in no certainty regarding the validity of making testaments by Indonesian citizens abroad. The author's suggestion is to revise the Indonesian Civil Code on several articles related to making testaments. In addition, it is necessary to establish an HPI law as protection in making testaments abroad, as well as the adoption of the concept of granting power of attorney by heirs to their heirs in Indonesia to register the testament with an Indonesian Notary.